A prospective cohort study of the safety of breast cancer surgery during COVID-19 pandemic in the West of Scotland. (February 2021) - Romics, Laszlo; Doughty, Julie; Stallard, Sheila; Mansell, James; Blackhall, Vivienne; Lannigan, Alison; Elgammal, Suzanne; Reid, Judith; McGuigan, Marie-Claire; Savioli, Francesca; Tovey, Sian; Murphy, Dermott; et al.
Abstract: Introduction: In order to minimise the risk of breast cancer patients for COVID-19 infection related morbidity and mortality prioritisation of care has utmost importance since the onset of the pandemic. However, COVID-19 related risk in patients undergoing breast cancer surgery has not been studied yet. We evaluated the safety of breast cancer surgery during COVID-19 pandemic in the West of Scotland region. Methods: A prospective cohort study of patients having breast cancer surgery was carried out in a geographical region during the first eight weeks of the hospital lockdown and outcomes were compared to the regional cancer registry data of pre-COVID-19 patients of the same units (n = 1415). Results: 188 operations were carried out in 179 patients. Tumour size was significantly larger in patients undergoing surgery during hospital lockdown than before (cT3-4: 16.8% vs. 7.4%; p < 0.001; pT2 – pT4: 45.5% vs. 35.6%; p = 0.002). ER negative and HER-2 positive rate was significantly higher during lockdown (ER negative: 41.3% vs. 17%, p < 0.001; HER-2 positive: 23.4% vs. 14.8%; p = 0.004). While breast conservation rate was lower during lockdown (58.6% vs. 65%; p < 0.001), level II oncoplastic conservation was significantly higher in order to reduce mastectomy rate (22.8% vs. 5.6%; p < 0.001). No immediate reconstruction was offered during lockdown. 51.2% had co-morbidity, and 7.8% developed postoperative complications in lockdown. There was no peri-operative COVID-19 infection related morbidity or mortality. Conclusion: breast cancer can be safely provided during COVID-19 pandemic in selected patients. Highlights: A regional prospective cohort study on safety of breast surgery during COVID-19 pandemic. Breast cancer surgery is safe in selected patients. No COVID-19 infection related morbidity and mortality detected.